1997
DOI: 10.1001/archpsyc.1997.01830240052008
|View full text |Cite
|
Sign up to set email alerts
|

The New York High-Risk Project

Abstract: The familial liabilities to schizophrenia and affective disorders show specificities and commonalities, differing markedly from each other in their expression of some disorders and sharing others. Patterns of comorbidity are generally, although not entirely, similar to these liabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(26 citation statements)
references
References 30 publications
0
23
0
3
Order By: Relevance
“…Although family studies have generally found these two disorders to ''breed true,'' a small degree of familial overlap has frequently been observed. Recent family study data have further supported some degree of overlap (44). Only the identification of specific genes will resolve this question.…”
Section: Discussionmentioning
confidence: 99%
“…Although family studies have generally found these two disorders to ''breed true,'' a small degree of familial overlap has frequently been observed. Recent family study data have further supported some degree of overlap (44). Only the identification of specific genes will resolve this question.…”
Section: Discussionmentioning
confidence: 99%
“…Our criterion diagnosis of SRI consists of several disorders that research has demonstrated to be both conceptually and genetically related to schizophrenia and includes schizophrenia, schizoaffective disorder, and Cluster A personality disorders (Erlenmeyer-Kimling et al, 1997). A premorbid group, consisting of individuals from the New York High-Risk Project (NYHRP; Erlenmeyer-Kimling & Cornblatt, 1988;Erlenmeyer-Kimling et al, 1984, 1997, was used to assess SzP's ability to identify individuals who would later (mean time to diagnosis ϭ 14 years) experience the onset of SRI. A postmorbid group, consisting of individuals from the Torrey-Gottesman National Institute of Mental Health (NIMH; Torrey, Bowler, Taylor, & Gottesman, 1994) study of identical twins discordant for schizophrenia, as well as members of Gottesman and Shields's (1972) Maudsley Twin Study, was created to test the construct validity of the scale.…”
Section: Methodsmentioning
confidence: 99%
“…Erlenmeyer- Kimling et al (1995), por su parte, ilustran la agregación familiar de los trastornos de personalidad del grupo A del DSM en descendientes de esquizofrénicos aunque, si bien diversos estudios refieren la presencia específica del trastorno esquizotípico de la personalidad (Pamas et al 1993;Maier, Lichtermann, Mingues y Heun, 1994), su trabajo revela la mayor prevalencia de los trastornos del grupo A (esquizotípico, paranoide y esquizoide) en conjunto. Algunos investigadores (como por ejemplo Siever, Keefe y Bernstein, 1991), observando la prevalencia del trastorno esquizotípico entre los familiares de pacientes no esquizofrénicos (Yeung, Lyons, Waternaux, Faraone y Tsuang, 1993), concluyen que no todos los casos de esquizotipia se encuentran genética-mente ligados a la esquizofrenia, con lo que sugieren que la relación personalidad esquizotípica-espectro esquizofréni-co, en términos de la teoría de conjuntos, tiene un carácter intersectivo, ya que aunque ambos conceptos comparten rasgos, ninguno de los dos contiene enteramente al otro.…”
Section: Precursores Conductuales Infantiles De La Esquizotipiaunclassified
“…Además, permiten la sistematicidad y uniformidad de las evaluaciones, con las ventajas que esto supone para conjeturar sobre posibles etiologías, asegurar la detección de todos los casos que presenten patología y corroborar el diagnóstico diferencial en presencia de ambigüedades Pamas et al, 1993;Erlenmeyer et al,1995).…”
Section: Introductionunclassified